An Overview of Biomass-Derived Graphene Oxide and Its Characteristics for Future Sustainable Applications - Wardana, Afif; Shahab, Ahmad Nabil; Dhaneswara, Donanta; Sofyan, Nofrijon (UI Scholars Hub, 2025)
The production of graphene oxide (GO) from biomass presents considerable promise as a sustainable alternative substitute for traditional semiconductors. Biomass waste, abundant and often underutilized worldwide, is distinguished by its high carbon content and regenerative characteristics, rendering it an optimal resource for sustainable material production. By heating its biopolymers, lignocellulosic biomass can be used as a new material to make graphene, which forms three-dimensional turbostratic crystallites. These crystallites, composed of partially defective aromatic carbon sheets with graphite-like characteristics, make it easier to create GO with specialized functions for cutting-edge applications. Its capability underscores the revolutionary potential of biomass waste in producing high-value products from otherwise overlooked resources . A number of manufacturing methods are carefully studied and tested to improve the structure and oxygen functionality of GO. These include catalytic ferrocene, Hummer's, modified Hummer's, catalytic acid spray (CAS), Tour's, and electrochemical exfoliation. Additionally, doping with non-metallic elements, including nitrogen, boron, sulfur, and phosphorus (e.g., N, B, S, P), is investigated to adjust the band gap and improve charge carrier mobility, all of which are essential for optimizing electro-optical performance in semiconductors. This study highlights the unexploited potential of biomass as a resource and establishes a foundation for the advancement of GO-based semiconductors, driving the development of more environmentally friendly, efficient, and sustainable electronic technology.